Remembering Repertoires: exploring performance as a social innovation technology - Rossouw, Tasneem (Department of Drama, 2019)
This thesis explores some of the functions that performance rituals play in social space. It proposes that these curated performance interventions may bring people together, and assist them in negotiating the past and their place in the present, in relation to that past. The possibility that through undergoing this process, these newly formed and/or strengthened communities are enabled to collectively build towards better futures, is also explored. Specifically, this work considers whether the ways in which this happens may qualify this applied form of performance intervention as a technology for Social Innovation. The study explores how the dynamic tensions between the document Archive (cf. Derrida, 1998)1 and the performance Repertoire (cf. Taylor, 2003)2 may contribute to this process. It further considers the roles of curatorial framing within this exchange. Elements of Case Study, Practice as Research, and Grounded Theory are combined to provide a methodological locus. The thesis counterpoints observations drawn from a case study, the Clanwilliam Arts Project, with two examples of the authoress’ own practice.